On the bumps and curves in the microband boundaries in a channel-die compressed Goss-oriented Ni single crystal - Afrin, N.; Quadir, Md Zakaria; Bassman, L.; Driver, J.; Albou, A.; Ferry, M. (2012)
The crystallographic alignment of microbands in a Goss oriented single crystal was investigated by two and three dimensional electron back scatter diffraction. The microband boundaries were found to be curved instead of being perfectly flat interfaces, and the overall alignment closely matched a potential slip plane. The bumps and curved were created during subsequent deformation and, thus, deviates the microband boundaries from crystallographic nature. © (2012) Trans Tech Publications, Switzerland.